Strategi Nelayan dalam Praktik Penangkapan Ikan Ramah Lingkungan, di Pantai Olo Belawan, Sumatera Utara - Meilinda Suriani Harefa; Elsa Kardina; Debora Saragih; Florensia Manik; Lilis Siagian; Melda Sihotang (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
This study aims to explore the strategies employed by local fishermen in practicing environmentally friendly fishing at Olo Beach, Belawan, North Sumatra. The research is motivated by the declining fish catches, which have raised collective awareness among the fishermen about the need to sustain marine ecosystems. Using a descriptive qualitative approach, data were collected through direct observation and in-depth interviews with selected fishermen. The findings reveal that fishermen have adopted several adaptive strategies, including limiting the number and size of fish caught, avoiding the use of destructive fishing tools, and maintaining the tradition of mutual cooperation in preparing fishing equipment. These strategies emerged from shared experience and community consensus, without formal government regulation. The results highlight the potential of grassroots initiatives in contributing to marine conservation. Therefore, it is essential for the government and related institutions to support these local practices through education, provision of sustainable fishing technology, and the development of alternative livelihoods for coastal communities.